2002
DOI: 10.1088/0953-8984/14/40/301
|View full text |Cite
|
Sign up to set email alerts
|

Sequential short-time propagation of quantum classical dynamics

Abstract: An algorithm for the simulation of quantum-classical dynamics is presented. Quantum-classical evolution is effected by a propagator exp(iLt) involving the quantum classical Liouville operatorL that describes the evolution of a quantum subsystem coupled to a classical bath. Such a mixed description provides a means to study the dynamics of complex many-body systems where certain degrees of freedom are treated quantum mechanically. The algorithm is constructed by decomposing the time interval t into small segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 28 publications
2
126
0
Order By: Relevance
“…In the adiabatic basis the QCLE leads to a surfacehopping-type solution where segments of classical evolution are interspersed with energy-conserving quantum transitions [40,50]. The QCL operator may be written in this basis as a sum of diagonal (adiabatic) and offdiagonal (nonadiabatic) parts,…”
Section: Theorymentioning
confidence: 99%
“…In the adiabatic basis the QCLE leads to a surfacehopping-type solution where segments of classical evolution are interspersed with energy-conserving quantum transitions [40,50]. The QCL operator may be written in this basis as a sum of diagonal (adiabatic) and offdiagonal (nonadiabatic) parts,…”
Section: Theorymentioning
confidence: 99%
“…18,[25][26][27][28][29][30]10 While the formal solution of this equation of motion is easily written as B W (t) ) exp(i Lˆt)B W (0), the construction of effective simulation algorithms for realistic many-body systems is not a simple task, and a number of different methods have been proposed. [29][30][31][32][33][34] In this paper, we describe a Trotter-based scheme for simulating quantum-classical Liouville dynamics in terms of an ensemble of surface-hopping trajectories. The method can be used to compute the dynamics for longer times with fewer trajectories than the sequential short-time propagation (SSTP) algorithm, which is also based on surface-hopping trajectories.…”
Section: B(t) ) Trb F(t) ) Trb (T)f(0)mentioning
confidence: 99%
“…Recently it has been shown that partially linearizing the propagator for the electronic degrees of freedom, giving rise to the partially linearized density matrix (PLDM) [7] approach and the forward-backward trajectory solution (FBTS) to the quantum-classical Liouville equation [8], allows more dynamical correlation to be included at relatively little additional cost to fully linearized methods. Introduc- * Electronic address: tmarkland@stanford.edu ing further dynamical correlations between the subsystem and the bath adds further accuracy, at the expense of assigning weights and phase factors to the trajectories [10][11][12]. This in turn adds many orders of magnitude to the number of trajectories, which grows rapidly with system dimensionality and time, that must be generated in order to obtain converged properties.…”
Section: Introductionmentioning
confidence: 99%